2021
DOI: 10.1029/2020gl089074
|View full text |Cite
|
Sign up to set email alerts
|

Climate Sensitivity Increases Under Higher CO2 Levels Due to Feedback Temperature Dependence

Abstract: Equilibrium climate sensitivity‐the equilibrium warming per CO2 doubling‐increases with CO2 concentration for 13 of 14 coupled general circulation models for 0.5–8 times the preindustrial concentration. In particular, the abrupt 4 × CO2 equilibrium warming is more than twice the 2 × CO2 warming. We identify three potential causes: nonlogarithmic forcing, feedback CO2 dependence, and feedback temperature dependence. Feedback temperature dependence explains at least half of the sensitivity increase, while feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
90
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 72 publications
(127 reference statements)
15
90
1
Order By: Relevance
“…Gregory et al, 2015). The values of  eff1pct and   1pct strongly depend on the formulation of 1pct ( ) F t for high forcing levels (e.g., Bloch-Johnson et al, 2020;Byrne & Goldblatt, 2014;Gregory et al, 2015 T quantified by M5 depending on first and last year of a linear regression of N on T (color shading) for the same ten abrupt4x simulations as in Figure 2. The standard deviation across the simulations is shown in hashed patterns; for example, a regression of years 100-220 results in a 5% error for the model mean (gray shading), but the standard deviation across the 10 models is still 10% (line hashing).…”
Section: 2mentioning
confidence: 96%
See 2 more Smart Citations
“…Gregory et al, 2015). The values of  eff1pct and   1pct strongly depend on the formulation of 1pct ( ) F t for high forcing levels (e.g., Bloch-Johnson et al, 2020;Byrne & Goldblatt, 2014;Gregory et al, 2015 T quantified by M5 depending on first and last year of a linear regression of N on T (color shading) for the same ten abrupt4x simulations as in Figure 2. The standard deviation across the simulations is shown in hashed patterns; for example, a regression of years 100-220 results in a 5% error for the model mean (gray shading), but the standard deviation across the 10 models is still 10% (line hashing).…”
Section: 2mentioning
confidence: 96%
“…Gregory et al, 2015). The values of eff1pct  and 1pct   strongly depend on the formulation of 1pct ( ) F t for high forcing levels (e.g., Bloch-Johnson et al, 2020;Byrne & Goldblatt, 2014;Gregory et al, 2015).…”
Section: Radiative Feedbacks and Their Implications For Estimating Ecs In Gcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new understanding of the state dependence of  cs E gives context to previous results. For example, Bloch-Johnson et al (2021) and Meraner et al (2013) attributed an increase in equilibrium climate sensitivity to the decrease in  cs E with warming. We expect these variations in  cs…”
mentioning
confidence: 99%
“…The equilibrium climate sensitivity (ECS) is defined as the increase in global‐mean surface temperature per doubling of normalCnormalO2 (IPCC, 1990). Several recent studies have demonstrated a robust increase in ECS in climates warmer than modern Earth due to state‐dependent feedback and forcing by normalCnormalO2 (Bloch‐Johnson et al., 2015; Bloch‐Johnson, Rugenstein, Stolpe, et al., 2020; Caballero & Huber, 2013; Colman & McAvaney, 2009; Hansen et al., 2005; Jonko et al., 2013; Leconte et al., 2013; Meraner et al., 2013; Popp et al., 2016; Romps, 2020; Russell et al., 2013; Seeley & Jeevanjee, 2021; Wolf & Toon, 2015; Wolf et al., 2018). When they investigate high enough temperatures, these studies find that the ECS reaches a maximum for global‐mean surface temperatures in the range of 310–320 K. We will refer to this as the “ECS bump.”…”
Section: Introductionmentioning
confidence: 99%